Analysis of Marketing Communication Strategies in Increasing Sales Volume of Rini's Cake During the Covid-19 Pandemic (A Social Science and Entrepreneurship Journal, 2021)
The purpose of this study was to Analysis of MarketingCommunication Strategies in Increasing Sales Volume ofRini's Cake During the Covid-19 Pandemic. The Covid-19pandemic occurred in Indonesia and all over the world, ofcourse, it has an effect on daily activities carried out, from anormal atmosphere to a new atmosphere or new normalwhich of course requires all parties to adapt again in order tosurvive. This happened in Rini's Cake's MSME businessmarketing process, so a study was carried out aimed atrestructuring the marketing communication strategy andlooking for creative ideas to increase sales volume in themidst of the Covid-19 pandemic. Thisresearch is a qualitativeexploratory research using purposive sampling method, thedata collected consists of primary data and secondary wereobtained from interviews, observations, reports sales andjournals before. The results of this study are that Rini's Cakehas a strategic design in increasing sales volume that hasbeen adjusted to the Covid-19 pandemic so that the salesvolume of Rini's Cake products can still go on and there is anincrease and this research indirectly complements theprevious research.
Keywords: Marketing communications; Marketing Strategy; Strategy; Sales volume; Pandemic Covid-19